2023
DOI: 10.15294/kemas.v18i3.32899
|View full text |Cite
|
Sign up to set email alerts
|

Level of Knowledge and Self Efficacy Improve Breast Self-Examination (BSE) Behaviors

Abstract: The incidence of breast cancer is 40 per 100.000 women. BSE is a screening to detect breast cancer. The research objective is to determine the correlation between knowledge and self-efficacy with BSE behavior. This cross-sectional descriptive-analytic study utilized a sample of 20-65 women aged 100 years. Multistage random sampling was used as the sampling technique—univariate and bivariate analysis with a significance level of ρ 0.05 and CI of 95%. The analysis results showed a correlation between the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The results of this study also found that educational group methods of investigation can improve the behavior of women of fertile age in BSE practice, this is in line with previous findings that there is a correlation between the level of knowledge and behaviour BSE p=0.02, Women who have high knowledge are times more likely to have BSE than women who have low awareness. Therefore, interventions to improve BSE behavior in women should be directed at increasing women's knowledge and awareness of the importance of BSE (Putri et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also found that educational group methods of investigation can improve the behavior of women of fertile age in BSE practice, this is in line with previous findings that there is a correlation between the level of knowledge and behaviour BSE p=0.02, Women who have high knowledge are times more likely to have BSE than women who have low awareness. Therefore, interventions to improve BSE behavior in women should be directed at increasing women's knowledge and awareness of the importance of BSE (Putri et al, 2023).…”
Section: Discussionmentioning
confidence: 99%